PENGARUH α- BENZIL AMINO PURINA DAN α- ASAM ASETAT NAFTALENA TERHADAP PEMBENTUKAN TUNAS TANAMAN NILAM (Pogostemon cablin Benth.) SECARA IN-VITRO - Rozaliana Rozaliana; Luthfi A Aziz Mahmud Siregar; Eva Sartini Bayu (Jurnal Agroekoteknologi, 2013)
This research aims to determined the concentration of the most effective growth regulator for budinduction patchouli plant by in-vitro methode. The research was done in the laboratory of planttissue culture, agriculture faculty university of north sumatra, medan from January 2012 to june2012 using factorial completely randomized design with 2wo factors that is giving BAP (0, 0.5, 1and 1.5 mg/l) and NAA (0, 0.2, 0.4 and 0.6 mg/l). The measured parameters were percentage ofeksplan living, the percentage of contamination, the percentage of eksplan forming buds, budheight, roots number, root length, leaves number, noods number, time of initiation, appearance ofcallus, colour of callus and texture of callus. The result showed that giving BAP and NAAsignificantly affected on the buds initiation time parameters with the best time of initiation is 7 days((0.6 mg/l NAA and 1.5mg/l BAP and the highest number of root that 8 pieces (0.2 NAA mg/l andBAP 1.5mg/l )and did not significanly on others parameter. The best medium for bud inductionwas not found yet.Key words : NAA, BAP, patchouli